Incidental Diagnosis of Bicornuate Uterus in a Lady of 48 Years - A Case Report (Delta Medical College Journal, 2022)
Congenital anomalies of uterus are not very uncommon. Quite a number of women with these anomalies can be totally asymptomatic. In some women, anomalies may be first detected during pregnancy or delivery. Here a case of incidentally diagnosed bicornuate uterus is reported in a lady of 48 years while being treated for breast carcinoma. The patient attended with a lump in her left breast at Delta Medical College Hospital, Dhaka, Bangladesh. She was totally asymptomatic previously and her three children were born preterm without any difficulty. Along with other investigations, abdominal ultrasonogram was done which showed two separate fundal and uterine cavities with single cervix. Bicornuate uterus was confirmed by endovaginal ultrasonogram. Breast carcinoma was treated accordingly.Delta Med Col J. Jul 2020 8(1): 46-50